ANALISIS SEGMENTASI DAN TARGET PASAR PENDIRIAN RUMAH SAKIT BUNDA MULYA KABUPATEN BOGOR - mufakhhir, Abdulaziez; Jati, Sutopo Patria; Arso, Septo Pawelas; Kartasurya, Martha Irene; Firman, Firman (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2024)
Introduction: The right marketing strategy is not only limited to promoting products, but also arranging segmentation, namely dividing product marketing based on target customers and target markets. Hospitals really need a marketing strategy to face all changes and challenges both internal and external to a company.Purpose: To analyze segmentation and determine the target market for the establishment of Bunda Mulya Hospital in Bogor RegencyMethods: Quantitative and qualitative research approaches (mixed methods). The quantitative approach used in this research is analytical observational with a cross sectional design. The qualitative approach in this research uses a grounded theory type of design. Market segmentation analysis was carried out to determine the appropriate target market for the establishment of Bunda Mulya Hospital through geographic, demographic, psychographic and behavioral approaches. The research subjects were the people of Bogor Regency, the Chair of PERSI Banten Province, Deputy Chair II of PERSI West Java Province, the Bogor Regency Health Service, and the Main Director of the Bunda Mulya Pratama Clinic.Results: The appropriate target market for establishing Bunda Mulya Hospital is the community around Bunda Mulya Hospital (travel time < 30 minutes) with an age range of teenagers - early adults (12-45 years), female, with a predominant high school/equivalent education level. by private workers, families of 2-4 people with total family income between 3-5 million. The public hopes to get fast treatment and complete specialist doctors. The community gets most of the information from neighbors/cadres/friends and visits 1-5x/year. The public provides suggestions regarding class I inpatient rates of <250,000, VIP class inpatient rates of <400,000, general practitioner consultation fees between 40,001-50,000, specialist doctor consultation fees between 100,001-125,000, normal delivery package costs between 1.5-2.5 million and The cost of an ultrasound examination is between 150,000-250,000. Most of the people around Bunda Mulya Hospital are willing to undergo examinations at Bunda Mulya HospitalConclusion: Plans for establishing a new hospital should pay attention to the needs of people of productive age (26-45 years), especially women. The public expects to receive fast service and complete specialist doctors. Therefore, this becomes input for Hospital Management to be able to meet community needs. Hospital financing should pay attention to the UMR limit for Bogor Regency where costs are adjusted for middle and lower middle class people